Praktikum en veldwerk - J.N. Papenfus (AOSIS, 1981)
Practical work is described as formal - planned practice and fieldwork offers the opportunity to carry out in a specific environment the essentials of systematically planned practical experience. In settling learning objectives, cognizance must be taken of the need to introduce affective aspects as well as connotive and psycho-motor components into practical teaching. Micro-teaching, interaction-analysis and simulated situations provide valuable practical teaching- learning opportunities and mention is made of evaluation procedures which may be applicable away from the hospital-ward situation.